Técnicas del grabado calcográfico aplicadas en gráficas relacionadas con la interpretación de leyendas tradicionales de la parroquia San Pedro de Vilcabamba - Lapo Guamán, Galo Efraín (2015)
The present investigation has like main objective the study of the techniques of chalcography engraving applied by the great masters, in order to create graphs related to the traditional legend interpretation of the parish San Pedro de Vilcabamba. To the being this one a theoretical-practical work, was used the analytical method for theoretical part, that allows to a better study of the techniques of chalcography engraving, whereas for the practical part the experimental method was used, at the time of making the graphical work; obtaining this way different results when combining several techniques of chalcography engraving in a same work. In the same way, at the end of the investigation it was managed to identify and to revalue the different traditional legend from the locality in study, that is transcribed in the present document and which they represented the base, from which was made the interpretation in graphical works